UNA EXTENSIÓN DEL MÉTODO SUBGRADIENTE PARA FUNCIONES CUASICONVEXAS - Navarro Rojas, Frank (2012)
In this work, we consider the problem of minimizing a quasiconvex, continue and Hölder function on the set optimal, not necessarily differentiable. We use the normalized direction of the normal con e of the set level of function and employ the stepsize rule based in knowledge of the optimal value of the objective function; we also present an example and us computational implementations in Matlab.